Amour et poésie dans La tumba de Antígona de María Zambrano - Margherita Camozzi (Cahiers de Civilisation Espagnole Contemporaine)
We aim to demonstrate, among other things, to what extent this work represented an original and free proposal. La tumba de Antígona is, in fact, in an in-between, "at the intersection of literary recreation" palimpsest Sophocles, and its philosophical interpretation. The logos of this Antigone is singular, not rational. His Word is a Poetic Word and at the same time, in his aspiration to transcendence, she speaks a philosophical logos. It is in this sense, that Zambrano's Antigone expresses, she says, a "desire for harmony of opposites", the philosopher speaks the language of Love.